Pengaruh Electronic Word of Mouth, Price Perception dan Brand Image Terhadap Repurchase Intention Pada E-commerce TiktokShop x Tokopedia di Kota Cimahi Jawa Barat. - Syaira Nur Hafifah; Hariyadi Triwahyu Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of electronic word of mouth, price perception and brand image on repurchase intention on E-commerce TiktokShop x Tokopedia in Cimahi City, West Java. The number of samples obtained was 120 respondents. The method used is quantitative, with data analysis techniques used are multiple regression analysis, classical assumption test, t test and F test using SPSS 27. The results showed that electronic word of mouth has a significant effect on repurchase intention, price perception has no significant effect on repurchase intention, brand image has a significant effect on repurchase intention. Electronic word of mouth, price perception and brand image have a positive effect simultaneously on repurchase intention.